EFFECT OF EMPOWERMENT AND JOB SATISFACTION ON COMMITMENT OF PRIVATE MIDDLE SCHOOL TEACHER ORGANIZATIONS IN EAST KARAWANG - Fitriana Nursyfa; Moch. Asmawi; - Suryadi (International Journal of Education, Information Technology, and Others, 2018)
The purpose of this study to 1) analyze the positive direct effect of empowerment on organizational commitment, 2) to analyze the positive direct effect of job satisfaction on organizational commitment, and 3) to analyze the positive direct effect of empowerment on job satisfaction. This study uses survey method with causal techniques. Population in the study was private junior high school teachers in East Karawang which amounted to 108 people, with a sample of 85 people. The research data was collected by research instrument in the form of questionnaire. Data analysis about the influence of other variables using quantitative approach while to explain the influence between variables using path analysis. The data collected were analyzed using path analysis (path analysis). The result of this research conclude that 1) empowerment have positive direct effect to organizational commitment, 2) job satisfaction have positive direct effect to organizational commitment, and 3) empowerment have positive direct effect to job satisfaction.